2021
DOI: 10.17755/esosder.853431
|View full text |Cite
|
Sign up to set email alerts
|

Pedagoji̇k Sevgi̇ Eği̇li̇mleri̇ Ölçeği̇ni̇n Uyarlanmasi: Geçerli̇k Ve Güveni̇rli̇k Çalişmasi

Abstract: Bu araştırmanın amacı Yin ve arkadaşları (2019) tarafından geliştirilen pedagojik sevgi eğilimleri ölçeğinin Türk kültürüne uyarlanmasıdır. Orijinal formu 6 boyut ve 29 madde olan ölçeğin uyarlama çalışmalarının ilk aşamasında dilsel eşdeğerlik çalışması yapılmıştır. Ölçeğin geçerlik ve güvenirlik çalışmaları için 892 sınıf öğretmeninden veri toplanmıştır. Yapılan açımlayıcı faktör analizinde, toplam varyansın %60,73' ünü açıklayan 5 boyutlu 26 maddelik ölçek elde edilmiştir. Yapılan doğrulayıcı faktör analizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Since each of the items in the scale is greater than .30, it is understood that each of the items has a high fit with the scale. Eroğlu and Kaya (2021), who obtained similar results at the end of the adaptation study of the "Pedagogical Love Tendencies Scale", calculated the Cronbach Alpha internal consistency coefficients for the reliability analysis of the scale as 0.88 for the bond and dedication dimension, 0.85 for the sincerity dimension, 0.80 for the class community and acceptance of diversity dimension, 0.90 for the empathy dimension, 0.88 for forgiveness, and 0.92 for the overall scale.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Since each of the items in the scale is greater than .30, it is understood that each of the items has a high fit with the scale. Eroğlu and Kaya (2021), who obtained similar results at the end of the adaptation study of the "Pedagogical Love Tendencies Scale", calculated the Cronbach Alpha internal consistency coefficients for the reliability analysis of the scale as 0.88 for the bond and dedication dimension, 0.85 for the sincerity dimension, 0.80 for the class community and acceptance of diversity dimension, 0.90 for the empathy dimension, 0.88 for forgiveness, and 0.92 for the overall scale.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…DSMQ: Schmitt et al (2013) developed this questionnaire in 2013. Eroğlu and Sabuncu (2018) conducted its Turkish validity and reliability study, and determined the Cronbach’s Alpha coefficient as 0.85. The DSMQ is rated a 4-point Likert type, ranging from 3 = “highly applies to me,” 2 = “considerably applies to me,” 1 = “slightly applies to me,” and 0 = “never applies to me.” The DSMQ has a total of 16 items and four subscales: Glucose Management (Items 1, 4, 6, 10, and 12), Dietary Control (Items 2, 5, 9, and 13), Physical Activity (Items 8, 11, and 15), and Health-Care Use (Items 3, 7, and 14).…”
Section: Methodsmentioning
confidence: 99%
“…The minimum and maximum scores of the scale are 0 and 10 points. A score close to 10 indicates an increase in diabetes self-management (Eroğlu & Sabuncu, 2018). The Cronbach’s alpha coefficient for DSMQ was found to be 0.71 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…To measure diabetes self-management skills, the DSMQ, which was developed by Schmitt et al (21) and adapted into Turkish by Eroğlu and Sabuncu (17), was used. The last 8 weeks of the individuals are taken into consideration and the individuals respond by thinking about it.…”
Section: Diabetes Self-management Questionnairementioning
confidence: 99%
“…In the literature, there are studies on medication self-efficacy (3,5), self-management (17) and type D personality (12,16) among patients with diabetes. However, no study has been found in the literature aiming at determining the relationship between medication self-efficacy, self-management, and type D personality in individuals with type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%